Physiological and Yield Responses of Wheat (Triticum aestivum) to Different Herbicide Treatments - Kawa A. Ali; Qadir, Muhsin H.; Rasoul, Samira O.; Ali, Saman S. (Sulaimani Journal for Pure and Applied Sciences, 2016)
A field study was conducted at Erbil agricultural research directorate to investigate the physiological and yield responses of wheat to five post emergence herbicides; Tribenuron-methyl; Pyroxsulam; mesosulfuron+ idosulfuron; Clodinafop-propargyl and Clodinafop-propargyl +Pinoxaden herbicides, while weed infested wheat plots and weed free wheat plots treated as controls. Results revealed significant increase of plant height when treated with Clodinafop-propargyl herbicide comparing to the lowest height in weed-free wheat plots. Number of spikes per meter square significantly increased with Pyroxsulam and reduced in weed infested wheat plots. Number of grains per spike and 1000 grains weight were at maximum levels in weed-free wheat plots and minimum levels were found with weed infested wheat treatments. Biological yield significantly increased with Clodinafop-propargyl herbicide, while Tribenuron-methyl caused a significant decrease of biological yield. All treatments caused a significant increase of economical yield compared with weed infested wheat plots. Chlorophyll content reduced in wheat plants after spraying herbicides showed sever reduction after spraying all studied herbicides with recovery process of photosynthetic pigments except with Pyroxsulam and mesosulfuron+ idosulfuron herbicides. According to EWRC scale the most efficient to less efficient herbicide arrangement will be as Clodinafop-propargyl +Pinoxaden, mesosulfuron+ idosulfuron, Pyroxsulam, Clodinafop-propargyland Tribenuron-methyl.
Keywords: Weed; Herbicide; Chlorophyll; Post emergence